Spermatozoon ultrastructure and sperm cryopreservation of the Brazilian dry season spawner fish pirapitinga, Brycon nattereri - Viveiros, Ana T. M.; Maria, Alexandre N.; Amaral, Thiciana B.; Orfao, Laura H.; Isau, Ziara A.; Verissimo-Silveira, Rosicleire [UNESP] (Wiley-Blackwell, 2012)
The aims of this study were to describe the fresh spermatozoon ultrastructure using scanning and transmission electron microscopy and to improve the sperm cryopreservation methodology for the freshwater fish pirapitinga Brycon nattereri. Extenders (BTS (TM) and NaCl), straw volumes (0.5 and 4.0 mL), thawing temperatures (30 and 60 degrees C) and activating agents (0.29% NaCl and 1% NaHCO3) were tested. Methylglycol was used as a cryoprotectant agent and sperm was frozen in nitrogen vapour (dry-shipper). Post-thawed sperm motility rate, motility quality (score 0=no movement; 5=rapidly swimming spermatozoa), duration of motility and spermatozoon morphology were evaluated. Fresh spermatozoon was 35.06 mu m long, the head was ovoid (2.00 x 1.22 mu m) with no acrosome, the midpiece was 2.15 mu m long and the flagellum was 30.90 mu m long with the typical 9+2 axoneme arrangement. Post-thawed sperm motility rate (7079% motile sperm), motility quality (score 3.1-3.7) and morphology (9.311.6% abnormal spermatozoa) were not affected by any of the parameters tested. The duration of sperm motility was longer when triggered in 1% NaHCO3 (3921031 s) compared with 0.29% NaCl (144338 s). Brycon nattereri sperm cryopreserved under the conditions described above yields over 70% motility and should last long enough to fertilize oocytes, even after 2 years of freezing.
Keywords: fish; semen; freezing; ultrastructure; Characiformes